2016
DOI: 10.1136/neurintsurg-2015-012209
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of device–clot interaction for stent retriever thrombectomy

Abstract: PurposeRapid revascularization in emergent large vessel occlusion with endovascular embolectomy has proven clinical benefit. We sought to measure device–clot interaction as a potential mechanism for efficient embolectomy.MethodsTwo different radiopaque clot models were injected to create a middle cerebral artery occlusion in a patient-specific vascular phantom. A radiopaque stent retriever was deployed within the clot by unsheathing the device or a combination of unsheathing followed by pushing the device (n=8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…Ideal interaction for successful thrombectomy is that the retrieval force transmitted to the thrombus by the SR device exceeds the inertial forces created by the friction between the clot and the vessel wall 24. During the thrombectomy, expansion of the SR causes embedding of the thrombus into the inner lumen of the device, which is referred to as integration of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideal interaction for successful thrombectomy is that the retrieval force transmitted to the thrombus by the SR device exceeds the inertial forces created by the friction between the clot and the vessel wall 24. During the thrombectomy, expansion of the SR causes embedding of the thrombus into the inner lumen of the device, which is referred to as integration of the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of the thrombus with the SR device depends on the size, length, and composition of the thrombus as well as the mechanical properties of the SR device. In vitro experiments demonstrated that the amount of thrombus integration was inversely correlated with the fibrin content of the thrombus 24. In addition, higher radial forces for a SR device are needed to penetrate a fibrin-rich thrombus than for a red-blood-rich thrombus 24 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distal end of the device is softer than that of the Solitaire FR 4×20 mm (deflection force measured to bend the distal tip of the stent retriever to 45°) and allows for an excellent vessel wall conformity and easy placement in tortuous and small caliber vessels. Similar to the other devices of the Trevo family, the large, non-overlapping stent cells permit maximum clot integration, even in smaller intracranial branches 15. In addition, the stent retriever has a hydrophilic coating, which reduces friction during use and is supposed to minimize endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…With standard deployment of stent-retrievers (i.e., passive unsheathing), the device's inherent radial force should theoretically ensure the compression of the clot against the vessel wall and subsequent clot migration through the stent struts into its lumen, 45,46 but oftentimes, standard deployment often results in insufficient wall apposition and clot integration (►Fig. 3).…”
Section: Optimizing Clot Integration: Active Push Deployment Of the Smentioning
confidence: 99%